Do expert swimmers have expert technique? Comment on "Arm coordination and performance level in the 400-m front crawl" by Schnitzler, Seifert, and Chollet (2011) - Havriluk, R. (Research Quarterly for Exercise and Sport, 2012)
In a recent article by Schnitzler, Seifert, and Chollet (2011), they used an index of coordination (IdC) to quantify arm synchronization in swimming, which has become a practical standard to measure gaps (negative IdC) and overlaps (positive IdC) in arm propulsion. Their previous work supported an increase in IdC as swimming velocity and performance level increase, consistent with mechanics and physiology. Their recent study showed a lower IdC for expert swimmers than for recreational swimmers and concluded "catch-up coordination can be an efficient coordination mode." In the hopes of preventing coaches and swimmers from using this finding to justify "catch-up stroke," other explanations are suggested.